A HUBUNGAN NILAI ALBUMIN SERUM DENGAN TINGKAT KEPARAHAN DAN LAMA RAWATAN PASIEN DM TIPE 2 DENGAN COVID-19 DI RSU BINA KASIH: HUBUNGAN NILAI ALBUMIN SERUM DENGAN TINGKAT KEPARAHAN DAN LAMA RAWATAN PASIEN DM TIPE 2 DENGAN COVID-19 DI RSU BINA KASIH - Tarigan, M.Bastanta; Situmorang, Nasib Mangoloi; Hutahaean, Reinhard (Universitas Methodist Indonesia, 2024)
Introduction Coronavirus disease 2019 (COVID-19) is an infectious disease that affects the respiratory system caused by Severe Acute Respiratory Syndrome Coronavirus (SARS-COV-2), which has become a health problem in Indonesia. The duration of treatment and the severity of COVID-19 will increase the risk of death and significant costs, which undoubtedly burden patients and the country. A marker is needed to determine the severity of the disease and the duration of treatment for COVID-19 patients with diabetes. Albumin is a protein that plays anti-inflammatory, antioxidant, anti-infection roles, and also participates in drug transfer within the human body. Poor glucose control, insulin resistance, insulin deficiency in type 2 diabetes (type 2 DM), and viral load in COVID-19 lead to hypoalbuminemia. Hypoalbuminemia will disrupt its function, leading to increased inflammation, oxidative stress, infection, and disturbance in drug distribution, thus hypoalbuminemia is suspected to play a role in increasing the severity and duration of treatment in type 2 DM patients with COVID-19. Method This study is an observational analytical study with a cross-sectional design conducted at Bina Kasih Medan General Hospital. The research subjects were type 2 DM patients infected with COVID-19 who underwent inpatient care from August to October 2021 with consecutive sampling that met the inclusion and exclusion criteria. Patients were categorized into moderate and severe severity levels. The duration of treatment was divided into less than and greater than or equal to 11 days, and serum albumin levels were evaluated. The independent variable was albumin, and the severity level and duration of treatment were dependent variables. The data used were secondary data from medical records, and bivariate analysis was performed to see the relationship between independent and dependent variables using the Chi-Chisqure test. Results During the period from August to October 2021, 82 subjects with type 2 DM who were infected with COVID-19 and underwent inpatient care were obtained. Out of 82 subjects who met the inclusion criteria, 34 subjects were included. Of the 34 study subjects, the majority were male, namely 26 subjects (76.4%), and 8 subjects (23.5%). Subjects who underwent inpatient care for <11 days were 15 (44.1%) and those who underwent inpatient care ≥11 days were 19 (55.9%). 18 subjects (52%) had moderate severity levels, and 16 subjects (47.05%) had severe severity levels. Based on the results of bivariate analysis, there was an inverse relationship between serum albumin levels and the severity of the disease (P <0.032), but there was no significant relationship between albumin levels and the duration of hospitalization (P <0.350). Conclusion A decrease in albumin levels is associated with the severity of the disease but not with the duration of treatment.